Streaming high-definition real-time video to mobile devices with partially reliable transfer - Wu, Jiyan (2019)
Delivering High-Definition (HD) real-time video to mobile devices is challenged with stringent constraints in delay and reliability. In the presence of network dynamics (e.g., channel errors and bandwidth fluctuations), the existing error-control mechanisms [e.g., Automatic Repeat reQuest (ARQ) and Forward Error Correction (FEC)] frequently induce deadline violations and quality degradations. To strike an effective balance between delay and reliability in real-time video transmission, this research presents an application-layer solution dubbed Partial rEliability based Real-timEStreaming (PERES) to perform partially reliable transfer. First, we develop an analytical framework to model the delay-constrained partial reliability for acknowledgement (ACK) and negative acknowledgement (NAK) based real-time video streaming. Second, we propose scheduling algorithms for video-aware reliability adaptation and network-adaptive buffer control. PERES is able to maximize the transmission reliability of high-priority video frames within stringent delay constraint. We implement the proposed transmission scheme in embedded video monitoring systems and evaluate the efficacy over different wireless network environments. Evaluation results demonstrate PERES achieves appreciable improvements over the reference schemes in perceptual video quality, delay performance, and bandwidth efficiency.